Credit growth and current account balance - Aysu Çelgin; Okan Eren; Pınar Özlü (Central Bank Review (CBR), 2023)
In this paper, we investigate the relationship between different loan types and the current account balance along with its sub-components. Our empirical results suggest that a rise in total loans inevitably leads to a deterioration in the current account balance. This relationship is preserved in the case of the goods trade balance, but it becomes statistically insignificant and disappears if the services trade balance is considered. When we examine different types of loans, our findings indicate that both consumer and corporate loans have sizeable and negative effect on both the current account and goods trade balances with the impact of consumer loans being much higher. We also report that only corporate loans have a significantly negative relationship with the services trade balance although the concurrent effect is rather small.
Keywords: F14; F31; 330; Credit growth; Current account balance; Goods trade balance; Services trade balance; Consumer loans; Firm or commercial loans